2015
DOI: 10.1007/s11096-015-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

A case of melphalan sustained accumulation in an 80-year old patient

Abstract: Case We report the case of melphalan accumulation in an 80-year old female with multiple myeloma. Her initial health status was good except for a moderate chronic renal failure (estimated glomerular filtration rate: 31 ml/min) and anemia. Among other drugs, her usual treatment included trimethoprim/sulfamethoxazole and the patient received melphalan from day 1 to day 4 for multiple myeloma. On day 13, she was admitted in intensive care unit for acute renal failure and severe sepsis with pancytopenia. Usual tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The results will be useful in investigating drug interactions; drugs that use similar transport mechanisms may affect each other's pharmacokinetics, resulting in altered cytotoxicity and differentially influence the clinical safety profile of cytotoxic agents, especially when used in high-dose chemotherapy. In fact, the pharmacokinetics of busulfan and melphalan, two DNA alkylating drugs used as part of pretransplant conditioning regimens, were altered in patients taking deferasirox and sulfamethoxazole [4, 7]. Based on our present study, the observed low clearance of busulfan and melphalan in these patients may be due to the inhibition of their efflux mediated by deferasirox and sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results will be useful in investigating drug interactions; drugs that use similar transport mechanisms may affect each other's pharmacokinetics, resulting in altered cytotoxicity and differentially influence the clinical safety profile of cytotoxic agents, especially when used in high-dose chemotherapy. In fact, the pharmacokinetics of busulfan and melphalan, two DNA alkylating drugs used as part of pretransplant conditioning regimens, were altered in patients taking deferasirox and sulfamethoxazole [4, 7]. Based on our present study, the observed low clearance of busulfan and melphalan in these patients may be due to the inhibition of their efflux mediated by deferasirox and sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 62%
“…The mechanistic nature of these interactions has not been fully characterized and the possible role of glutathione (GSH), known to be involved in Bu metabolism, remains undetermined. Melphalan (Mel), another DNA alkylating agent, was found to accumulate in a multiple myeloma patient taking sulfamethoxazole [7]. In an earlier report, flunarizine, a diphenylpiperazine calcium channel blocker, enhanced Mel cytotoxicity against rhabdomyosarcoma xenograft, which the authors attributed to possible modification of transport mechanisms responsible for cellular Mel retention, but without providing supporting data [8].…”
Section: Introductionmentioning
confidence: 99%
“…Melphalan clearance may be decreased in patients with RI and subsequent progression from RI to renal failure has been reported in a patient receiving treatment for multiple myeloma 71. Dose reductions of 50% are recommended for patients with moderate RI (CrCl 30–50 mL/min) who are not scheduled to receive hematopoietic stem cell transplantation (HSCT), but it should not be used in patients with more severe RI (CrCl <30 mL/min; Table 2).…”
Section: Considering Renal Risk While Managing Cancermentioning
confidence: 99%